UPAYA MENGURANGI TANTRUM MELALUI BERMAIN BOLA BAGI ANAK AUTIS DI SLB FAN REDHA PADANG - Estri -; Amsyaruddin -; Asep Ahmad Sopandi (Universitas Negeri Padang, 2013)
Abstract This research background in the presence of a child with autism X tantrums are still problematic in the process of learning (children often have tantrums in the study). Based on this research aims to reduce tantrum behavior that children learn best, and see if the exercise ball games can reduce tantrum behavior. This study uses a single sabject research (SSR) with the AB design. Subjects were children with autism X in SLB Fan Redha padang. Assessment in this study is consistent and measured the length of children do not have tantrums before and after treated with ball play exercises presented in the form of duration. These results indicate that the behavior of children with autism tantrums X decreases, initially at baseline conditions conducted in eight sessions children have tantrums for a few minutes, on the condition that intervention sessions were 12 child tantrum behavior can be reduced so that in a few minutes the child has a tantrum and further reduced from second to second child has a tantrum. Data was colleted using a test that the child was asked to do the exercises play ball. Trus the proven formula that issues raised missed playing football practice effective ways to reduce tantrum behavior for children with autism X in Fan Redha Padang. The results in children autism X playing ball in can reduce tantrum behavior, the research suggest the teacher to use the execise ball to play in reducing tantrums for future learning. Kata Kunci : tantrums ; upaya ; mengurangi tantrum ; bermain bola.